2021
DOI: 10.3389/fphar.2021.779652
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Podocytes DPP4 Activity Is a Potential Mechanism of Lobeliae Chinensis Herba in Treating Diabetic Kidney Disease

Abstract: Diabetic kidney disease (DKD) is the leading cause of end-stage renal disease and has become a serious public health problem worldwide. Dipeptidyl peptidase-4 (DPP4) inhibitors, an emerging drug for the treatment of diabetes, have been found to have renoprotective effects in addition to glucose-lowering effects and therefore have the potential to be a treatment modality for DKD. Lobeliae Chinensis Herba (LCH), a traditional Chinese herb widely used in the treatment of diabetes, has recently been found to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…Our data showed decreased expressions of nephrin and WT1, accompanied by foot processes fusion and glomerular basement membrane thickening in the kidneys of db/db mice, which were significantly ameliorated with KPF treatment, showing the protective effect of KPF on podocyte in DN. This finding in our study was consistent with the previous findings by Yuanping Li et al (30), and Xinyu Wang et al (31), which showed the inhibition effect of KPF on podocyte apoptosis under hyperglycemic conditions in vitro. Impaired autophagy mediated imbalance of homeostasis in podocytes, contributing to podocyte dysfunction and further renal injury in DN (32).…”
Section: Discussionsupporting
confidence: 94%
“…Our data showed decreased expressions of nephrin and WT1, accompanied by foot processes fusion and glomerular basement membrane thickening in the kidneys of db/db mice, which were significantly ameliorated with KPF treatment, showing the protective effect of KPF on podocyte in DN. This finding in our study was consistent with the previous findings by Yuanping Li et al (30), and Xinyu Wang et al (31), which showed the inhibition effect of KPF on podocyte apoptosis under hyperglycemic conditions in vitro. Impaired autophagy mediated imbalance of homeostasis in podocytes, contributing to podocyte dysfunction and further renal injury in DN (32).…”
Section: Discussionsupporting
confidence: 94%
“…Dipeptidyl peptidase 4 (DDP4) is specifically upregulated in DKD podocytes, which may be related to podocyte proliferation. Through analysis of the TCM Systematic Pharmacology database, it was found that quercetin, methyl rosmarinate, kaempferol, diosgenin, and Acacia may inhibit DPP4 activity and the proliferation of DKD podocytes ( Wang et al, 2021 ). High-dose Tripterygium wilfordii can improve the overexpression of nephrin in adriamycin-treated rats and inhibit abnormal proliferation of podocytes so as to reduce proteinuria and glomerulosclerosis ( Wan et al, 2014 ).…”
Section: Protective Effects Of Traditional Chinese Medicine and Activ...mentioning
confidence: 99%
“…ex DC.) Wight & Arn., 9 quercetin, diosmetin, methyl rosmarinate, kaempferol, and acacetin from Lobelia chinensis Lour., 10 yam ( Dioscorea alata L. cv. Tainong No.…”
Section: Introductionmentioning
confidence: 99%